Are Influencers’ Causes Authentic? How Influencer-Cause Fit Shapes Followers’ Attitudes- Abstract - Herter, Márcia (2020)
Herter, M., Pinto, D. C., Soares, R., Abreu, C., & Leal, M. D. C. (2020). Are Influencers’ Causes Authentic? How Influencer-Cause Fit Shapes Followers’ Attitudes- Abstract. In Proceedings of the Regional European Marketing Academy Conference, 11th (pp. 1-2). European Marketing Academy (EMAC). http://proceedings.emac-online.org/pdfs/R2020-84332.pdf